2004
DOI: 10.1093/eurpub/14.4.398
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of disability pension in long-term sickness absence: Results from a population-based and prospective study in Norway 1994-1999

Abstract: In addition to previously known socio-demographic predictors, medical variables were important in identifying sickness absentees with an increased risk of DP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
93
1
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 38 publications
15
93
1
5
Order By: Relevance
“…19,32,33 Less control of working conditions increases the burden on employees, especially on women in low-paid jobs. 19 The present study confirmed findings of no sex difference in relation to the risk of transition from sickness absence to disability pension, 22,30,34 implying that the threshold for taking sick leave is not lower among women than men.…”
Section: Comparison With Existing Literaturesupporting
confidence: 86%
“…19,32,33 Less control of working conditions increases the burden on employees, especially on women in low-paid jobs. 19 The present study confirmed findings of no sex difference in relation to the risk of transition from sickness absence to disability pension, 22,30,34 implying that the threshold for taking sick leave is not lower among women than men.…”
Section: Comparison With Existing Literaturesupporting
confidence: 86%
“…Irrespective of their length, sickness periods increase the risk for subsequent work absence (Helgesson et al 2016). In the long term, sickness absence increases the risk of adverse economic and social conditions (Bryngelson 2009), predicts disability pension (Gjesdal et al 2004;Kivimäki et al 2007), and signifies the risk of becoming unemployed (Virtanen et al 2006). The demographic change, and especially the decrease of the working-age population, emphasizes the need to reduce sickness absence and lengthen work careers.…”
Section: Introductionmentioning
confidence: 99%
“…A Norwegian attempt to tighten eligibility criteria for disability benefits has mostly affected women, people with little formal education, and those with 'medically imprecise' diagnoses (Claussen 1998). Even if regulations regarding disability pensions vary considerably across countries and over time, poor health remains the prime factor in the granting of such pensions (Gjesdal et al 2009;Gjesdal et al 2004;Hult et al 2010). Hence, in order to reduce societal costs for disabilities and prevent the marginalisation of individuals, it would be useful to identify the healthrelated mechanisms causing a person to prematurely leave the labour market.…”
Section: Introductionmentioning
confidence: 99%
“…In most countries, women are under-represented in contributory disability programmes; the opposite is true in the Nordic countries, which have a high level of female employment (Stattin 2005). Risk patterns have been shown to vary by gender with regard to physiological disease markers (Straface et al 2010), 5 occurrence of disease (Östergren et al 2005), and societal factors behind disability pension awards (Gjesdal et al 2004). Therefore, analyses were stratified by gender.…”
Section: Introductionmentioning
confidence: 99%